Eighteenth-Century Indian Muraqqaʿs : Audiences - Artists - Patrons and Collectors - Weis, Friederike, (Islamic Manuscripts and Books ;, 2025)
Fourteen essays and one appendix discuss numerous eighteenth-century Indo-Persianate albums ( muraqqaʿs ) consisting of folios with paintings, calligraphic pieces, and elaborate decorative margins. These albums - now in Berlin, Baroda, London, Paris, and Manchester - were assembled for or collected by the Mughal nawabs of Awadh (Uttar Pradesh), local elites in Bengal and Bihar, as well as Europeans. The book not only presents hitherto rarely investigated material, but also provides general information and many new discoveries based on first-hand codicological study and historical research. It will significantly expand our knowledge of the production, collecting practices, and audiences of muraqqaʿs in eighteenth-century India.